Pengaruh Pendidikan Gizi Melalui Buku Saku Tentang Diet Anak Autisme Terhadap Pengetahuan Ibu Di Sekolah Luar Biasa Di Kota Mataram - Lolita Nurarista (Poltekkes Kemenkes Mataram, 2017)
Background. Steps to reduce the symptoms of autism sufferers is one of them is diet diversion. Mothers are the main actors in the family in the decision making process, especially those related to food consumption. By having knowledge of nutrition, especially nutrition needed for children with autism, mothers can develop a pattern of good food consumption for children with autism. Pocket books are one of the media that can be used in providing nutrition education, which is a medium for conveying health messages in the form of books, both in the form of writing and drawing. Research Purposes. To find out the Effect of Nutrition Education through a Pocket Book on the Autism Child Diet on Mother's Knowledge in Extraordinary Schools in the City of Mataram. Research Methods. Pre-experimental research design with the design form of one group pretest posttest design for all autistic students in the Mataram School of Special Assessor. The research sample was 29 people. Interventions in the form of providing nutrition education through a pocket book on the diet of children with autism. The instruments used were questionnaires and pocket books. Data analysis used is univariate and bivariate. Research Result. The results showed that before giving nutrition education through pocket books, most respondents had a level of knowledge in the less category as many as 26 respondents (89.7%). after being given nutrition education through a pocket book most respondents had a level of knowledge in the moderate category as many as 18 respondents (62.1%). The Wilcoxon test results obtained p value = 0,000 <α = 0.05. Conclusion. There is a significant influence between nutritional education through a pocket book about the diet of autistic children towards the knowledge of mothers in special schools in the city of Mataram.